Limiting source dimensions of three-dimensional analytical point source model for solute transport - Ahsanuzzaman, A. Noman M., author; Kolar, Randall, author; Zaman, Musharraf, author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
This article presents a criterion for limiting source dimensions of the instantaneous point source model. The source dimensions are required for applying superposition of the point sources in space to represent the non-point sources. The criterion generates less than one percent error when compared to the existing finite source model. A comparison between the existing point and the finite source models is conducted. It is found that the finite source model does not give acceptable output at all times, if series distribution is used to compute the error function. The front and tail of the concentration breakthrough curve from the finite source model shows uncharacteristic output depending on the source dimension and the distance of the observation point. On the contrary, the point source model generates smooth breakthrough curves at all time.
Hydrology days 2003
AGU hydrology days 2003
23rd annual AGU hydrology days was held on March 31 - April 2, 2003 at Colorado State University.